Facilitation of the Kinetics of Alkaline Water Electrolysis on Polycrystalline Nickel Electrode by Introduction of Acetone to 0.1 M NaOH Working Solution - Mateusz Kuczyński; Tomasz Mikołajczyk; Bogusław Pierożyński; Bartosz Pszczółkowski (Applied Sciences)
The current work examines the effect of acetone on the electrochemical characteristics of a polycrystalline nickel electrode in a 0.1 M NaOH electrolyte, with respect to the kinetics of alkaline water electrolysis (HER: hydrogen evolution reaction, and OER: oxygen evolution reaction). Cyclic voltammetry (CV) and impedance spectroscopy (EIS) electrochemical techniques were employed to examine these processes for acetone concentrations stretching from 1.0 × 10−7 to 1.0 × 10−3 M. The introduction of small amounts of (CH3)2C=O clearly facilitated the catalytic efficiency of both examined electrochemical gas evolution processes. The latter is believed to result from a significant reduction in the surface tension parameter, due to the mutual interactions of acetone and water molecules, thus facilitating the detachment of gas bubbles from the nickel electrode surface. These findings suggest considerable opportunities for the introduction of tiny amounts of organic additives into alkaline electrolytes to improve the industrial alkaline water electrolysis process that is performed on technologically valuable electrode materials.